China’s roadmap for fostering S&T and catalyzing innovation: lessons for India - Sandhya, G. D; Nath, Pradosh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT)
In the past three decades since the advent of market oriented reforms began in 1978, China has made rapid strides in catalyzing economic growth. The economic development coincides with the development of significant capabilities in several areas of science, technology, and innovation. China has recorded notable achievements in a number of emerging fields. This paper investigates the process that has catalyzed the developments in Science and Technology (S&T) and the key factors that have facilitated this process. The causality of dynamism of S&T in China points at targeted development, an emphasis on high growth industries and high technology, commensurate resource mobilization, ruthless restructuring of innovation actors, dynamic organization and management of R&D, continuously evolving policies with strict enforcement, and implementable instruments. This paper attempts to bring out the roadmap of the Chinese transformation process in S&T and derive policy lessons for India.